The perception of employees about the regulatory environment in the tourism industry: Insights from Nepal (Nepalese Journal of Hospitality and Tourism Management, 2020)
This paper aims to explore the perceptions of tourism employees on the role of regulatory environment including the government in promoting employees’ welfare. Despite a need for an examination of employees’ voice in the formulation of employment policies and in their implementation by a government, no or very little literature specifically dealing with this topic has been found during the present study. This paper is an attempt to fill this gap. Based on an in-depth semi-structured interview with hotel and airline employees in Kathmandu (Nepal), this paper hammers out three key aspects of the regulatory environment that may affect employees’ welfare, viz., efficiency of labour law, government’s attitude towards tourism labour, and judicial process and system. The paper discusses the implications of these findings for the tourism industry as well as for the government in developing countries.